(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: A chronic subdural hematoma (CSDH) is defined as an encapsulated accumulation of a clot of blood and degraded blood products on the surface of the brain between the dural and arachnoid membranes. Papilledema had for a long time been referred to as a characteristic objective symptom of CSDH. The incidence of papilledema is however, variable and depends on a variety of factors. Purpose: To analyze the data on the diagnosis of papilledema in patients with CSDH and to review the place of papilledema among the clinical findings in CSDH. Material and Methods: We retrospectively reviewed the medical records of 164 patients with CSDH who underwent treatment at the Romodanov Neurosurgery Institute and Zaporizhzhia City Clinical Emergency Care Hospital from 2011 through 2021. Patients underwent clinical-and-neurological, ophthalmological, and neuroimaging examinations. Results: Papilledema was found in 4 (2.4%) of the patients. All these four patients had moderate papilledema which regressed after surgery. Details of these cases were reviewed. Conclusion: A shift in the peak incidence of CSDH towards an older age group and an increasing use of neuroimaging modalities exert an impact on the incidence of papilledema in patients with CSDH. Papilledema was found in 2.4% of the patients of the study.